The Impact of the Farming Insurance Program on the Efficiency of Lowland Rice Farming in Rias Village, South Bangka Regency - Rati Purwasih; Rostiar Sitorus; Eni Karsiningsih; Yulia (Perum BULOG, 2023)
The rice farming insurance program (AUTP) aims to support farmers in their rice production. This study aimed to analyze the effect of farmers’ participation in the AUTP program on the technical efficiency of lowland rice farming in Rias Village. The sample was determined using purposive sampling, which included 30 AUTP participants and 30 non-AUTP participants. The data was analyzed using the stochastic frontier production function and independent sample t-test. The results showed that the total surface area of farming, the amount of phosphorus and potassium fertilizer significantly affected rice production (α = 5 percent). Average value of technical efficiency of lowland farming was 0.50 (AUTP participating farmers) and 0.34 (non-AUTP participating farmers), which was below the threshold of the average technical efficiency (0.70). Thus, lowland rice farming was technically inefficient. The lowland rice farming of AUTP participants was slightly more efficient than non-AUTP participant farmers, but was not enough to redeem efficiency. Farmers’ age, education, number of family of farmers, duration of farmers joined a farmers group and farmers’ participation in the AUTP programs had significant effects on TE in lowland rice farming (α = 5 percent). Intensive assistance from the agricultural extension workers regarding the technical management of lowland rice farming would be beneficial.